Analisa Transaksi Perdagangan Saham pada Pasar Sekunder - Abdurohim Abdurohim (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2021)
Abstract This study aims to analyze the trading of stock transactions on the secondary market in Indonesia during the compared October 2018 to 2021, by analyzing the stock trading on the IDX, the results of the shares traded in the October 2018-2021 period experienced price fluctuations with a tendency to increase significantly. With the dynamics of the changing global and national economic environment, as well as stock trading transactions during the four-year period, the volume of transactions on the IDX increased, despite the COVID-19 outbreak, natural disasters such as flash floods, national economic growth experiencing a sharp decline and policies the government in normalizing the economy such as the United States (USA) will implement a tapering policy, so that this condition affects the decisions of IDX investors in buying and selling shares. Abstrak Perdagangan saham di pasar sekunder di Indonesia selama bulan Oktober 2018 sampai 2021 yang diperbandingkan, dengan melakukan analisis terhadap perdagangan saham di BEI tersebut diperoleh hasil saham yang diperdagangkan pada periode Oktober 2018-2021 mengalami fluktuasi harga kecenderungan meningkat, signifikan dengan dinamika lingkungan ekonomi baik global maupun nasional yang berubah-ubah, serta transaksi perdagangan saham selama periode empat tahun tersebut volume transaksinya di BEI meningkat, meskipun terjadi wabah penyakit covid-19, bencana alam seperti banjir bandang, pertumbuhan ekonomi nasional mengalami penurunan tajam serta kebijakan pemerintah dalam menormalkan perekonomian seperti Amerika Serikat (USA) akan menerapkan kebijakan tapering, sehingga kondisi ini mempengaruhi keputusan para investor BEI dalam melakukan pembelian dan penjualan saham.